Motivational Interviewing for encouraging quit attempts among unmotivated smokers: study protocol of a randomized, controlled, efficacy trial - Catley Delwyn; Harris Kari; Goggin Kathy; Richter Kimber; Williams Karen; Patten Christi; Resnicow Ken; Ellerbeck Edward; Bradley-Ewing Andrea; Malomo Domonique; Liston Robin (BMC, 2012)
Abstract Background Although the current Clinical Practice Guideline recommend Motivational Interviewing for use with smokers not ready to quit, the strength of evidence for its use is rated as not optimal. The purpose of the present study is to address key methodological limitations of previous studies by ensuring fidelity in the delivery of the Motivational Interviewing intervention, using an attention-matched control condition, and focusing on unmotivated smokers whom meta-analyses have indicated may benefit most from Motivational Interviewing. It is hypothesized that MI will be more effective at inducing quit attempts and smoking cessation at 6-month follow-up than brief advice to quit and an intensity-matched health education condition. Methods/Design A sample of adult community resident smokers (N = 255) who report low motivation and readiness to quit are being randomized using a 2:2:1 treatment allocation to Motivational Interviewing, Health Education, or Brief Advice. Over 6 months, participants in Motivational Interviewing and Health Education receive 4 individual counseling sessions and participants in Brief Advice receive one brief in-person individual session at baseline. Rigorous monitoring and independent verification of fidelity will assure the counseling approaches are distinct and delivered as planned. Participants complete surveys at baseline, week 12 and 6-month follow-up to assess demographics, smoking characteristics, and smoking outcomes. Participants who decide to quit are provided with a self-help guide to quitting, help with a quit plan, and free pharmacotherapy. The primary outcome is self-report of one or more quit attempts lasting at least 24 hours between randomization and 6-month follow-up. The secondary outcome is biochemically confirmed 7-day point prevalence cessation at 6-month follow-up. Hypothesized mediators of the presumed treatment effect on quit attempts are greater perceived autonomy support and autonomous motivation. Use of pharmacotherapy is a hypothesized mediator of Motivational Interviewing's effect on cessation. Discussion This trial will provide the most rigorous evaluation to date of Motivational Interviewing's efficacy for encouraging unmotivated smokers to make a quit attempt. It will also provide effect-size estimates of MI's impact on smoking cessation to inform future clinical trials and inform the Clinical Practice Guideline. Trial registration ClinicalTrials.gov NCT01188018